1981
DOI: 10.1161/01.cir.64.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Impaired left ventricular diastolic filling in patients with coronary artery disease: assessment with radionuclide angiography.

Abstract: To assess left ventricular (LV) diastolic filling at rest in patients with coronary artery disease (CAD), we analyzed high-resolution time-activity curves (10-20 msec/frame) obtained from gated radionuclide angiograms in 231 patients. Peak LV filling rate (PFR), expressed in end-diastolic volumes per second (EDV/sec), was subnormal in CAD patients (1.8 +/- 0.6 [+/- SD] vs normal mean of 3.3 +/- 0.6, p les than 0.001) and time to PFR (TPFR), measured from end-systole to PFR, was prolonged (171 +/- 41 msec vs no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
142
5
9

Year Published

1986
1986
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(164 citation statements)
references
References 33 publications
8
142
5
9
Order By: Relevance
“…',',"' Based on experimental and clinical evidence that the impairment of left ventricular relaxation may occur before systolic dysfunction in many disease states,1'5 and based on the assumption that the rate of ventricular relaxation is an important determinant of early diastolic filling, many clinicians have attempted to determine early abnormalities in left ventricular relaxation by estimating early filling function, and in particular, by using the PRFR as an index.7', 10,11,13,14,16 The loading interventions used in this study, increased preload and afterload, are known to change the rate of left ventricular relaxation in ways that are consistent with the results of this study (see Brutsaert et al',2 for reviews). However, we do not know what these interventions would do to diastolic function in the diseased heart, nor do we know how changes in the rate of isovolumetric relaxation will affect diastolic events after the onset of filling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…',',"' Based on experimental and clinical evidence that the impairment of left ventricular relaxation may occur before systolic dysfunction in many disease states,1'5 and based on the assumption that the rate of ventricular relaxation is an important determinant of early diastolic filling, many clinicians have attempted to determine early abnormalities in left ventricular relaxation by estimating early filling function, and in particular, by using the PRFR as an index.7', 10,11,13,14,16 The loading interventions used in this study, increased preload and afterload, are known to change the rate of left ventricular relaxation in ways that are consistent with the results of this study (see Brutsaert et al',2 for reviews). However, we do not know what these interventions would do to diastolic function in the diseased heart, nor do we know how changes in the rate of isovolumetric relaxation will affect diastolic events after the onset of filling.…”
Section: Discussionmentioning
confidence: 99%
“…3' 4, 7, 12, 14 Because this direct index of isovolumetric relaxation requires an invasive measurement of left ventricular pressure, many investigators assume that left ventricular relaxation can be assessed indirectly by estimating early diastolic filling. For example, peak rapid filling rate (PRFR) has been derived from radionuclide angiography, 10 11, 16 peak rates of chamber or wall dimension change have been measured from M mode echocardiograms,6, 9 15 and peak rapid filling velocity has been determined with Doppler ultrasound. '3 These approaches are based on the principle that the falling ventricular pressure contributes to the generation of the atrioventricular pressure difference that accelerates the blood across the mitral valve.…”
mentioning
confidence: 99%
“…The peak filling rate was normalized to end-diastolic volume and was calculated as the slope of the filling curve between two "cursors" placed 80 ms apart to give the greatest rate of filling. The time to peak filling rate was the distance from end-systole to the midpoint of the segment of curve used for measurement of peak filling rate (Bonow et al, 1981a;Mancini et al, 1983). Blood pressure was measured with a calibrated mercury sphygmomanometer using standard techniques.…”
Section: Ventricular Function Assessmentsmentioning
confidence: 99%
“…[23][24][25] Earlier studies have demonstrated the presence of abnormal diastolic function in patients with CAD without evidence of systolic wall motion abnormalities by radionuclide angiography or digitized cineangiography. [26][27][28] Kondo et al have also demonstrated that delayed outward LV wall motion in the isovolumic relaxation phase by digital subtraction high-frame-rate echocardiography was indicative of CAD. 29 In our experience, a positive myocardial velocity occurring during the isovolumic relaxation phase as detected by the spectral tissue Doppler mapping technique (MOMI) was indicative of critical coronary artery stenosis in patients complaining of chest pain with visibly normal LV contraction.…”
Section: Discussionmentioning
confidence: 98%